Assessment in medical ethics training of medical interns 2003, Universidad Nacional Mayor de San Marcos - Zavala, Salomón (2007)
Objective: To determine the medical interns training in medical ethics. Design: Qualitative in cipher study of professional skill tests. Setting: Universidad Nacional Mayor de San Marcos’ Human Medicine Professional Academic School. Participants: Interns of medicine, year 2003. Interventions: Secondary source of information related to the results of professional skills examination taken to medical interns graduated in 2003, at Universidad Nacional Mayor de San Marcos was used. Responses to the question in regards to information to patients and their families, and ethical issues of the clinical cases were analyzed. Classification criteria was designed and each was quantified from 0 = no mention to 3 = much mention. Two researchers participated in the classification process. Main outcome measures: Information to patients and their families, and ethical issues. Results: The proportion male/female was 2/1 in the whole population. The mean age was 27,2 (SD 3,37); the youngest age was 23 and the oldest 43; the greatest percentage of interns was between 25 to 29 yearold. Most answers did not mention explicit veracity in information to the patients and their families (92%), informed consent (96%), patient-physician relationship (92%), other relationships (95%). Qualitative analysis showed therapeutic effort limitation and ethics of intimate physical examination. Conclusions: Veracity in information to patients and their families, informed consent, patient-physician relationship and other relationships were themes that will require special training.